Ephraim Hochhauser a nově objevené malby z Trěště příspěvek k problematice zkoumání portrétní malby raného novověku - Macurová, Zuzana (2021)
The article presents a newly identified set of portraits painted in the 1740s and 1750s by Ephraim Hochhauser (1691–1771), portraitist and member of the Vienna Academy of Arts. The paintings presented come from the château at Třešť and are today stored in the state château of Jaroměřice nad Rokytnou. The portraits depict prominent personalities of the military and political world of the 17th century and the first half of the 18th century, as well as several members of aristocratic families. Today, the collection consists of twenty-one canvases, with twenty works having a signature and date on the reverse. The client for this extensive and long-term commission was probably Field Marshal Philipp Ludwig von Moltke (1693–1780). It can be assumed that Ephraim Hochhauser also painted some of the other surviving portraits from the château at Třešť. However, the poor state of many of the canvases makes it impossible to make any more precise judgements about their authorship
Keywords: Hochhauser, Ephraim -- 1691-1771; Bildnismalerei; Schloss; Schloss Jaroměřice -- Jaroměřice nad Rokytnou; Třešt